Teenage time use and educational attainment in adulthood in Finland - Ojala, S; Kan, M-Y; Oinas, T (MDPI, 2021)
We investigated the role of teenage everyday social ties in educational outcomes by examining the association between teenage time use and educational attainment in adulthood. The sample consisted of young people aged 10–18 from the 1979 Finnish Time Use Survey, and the same respondents’ educational attainment later in life recorded from population register data at the year of 40th birthday (n = 366 men and 393 women). We assessed the associations of time spent with the parents, on studying, leisure activities, as well as social connectedness with friends and participation in extracurricular activities, with educational outcomes. Our findings indicated that time spent with the father is positively associated with the likelihood of completing tertiary education for both daughters and sons. In particular, time spent with lower-education fathers was associated with teenagers’ future tertiary education. However, intense friendships and participation in extracurricular activities were not associated with academic achievement later in life. The findings suggest that educational attainment is partly explained by teenage time spent with the family. Less-educated fathers can enhance the attainment of higher education of their children by spending more time with their teenage children.